A study on microclimate monitoring and control inside greenhouse using fans automation - Irfan Ardiansah; Endryaz Vergian Nusantara; Selly Harnesa Putri; Ryan Hara Permana (Institute of Advanced Engineering and Science, 2024)
Efficient microclimate management is crucial in enhancing crop yields in greenhouses. Factors like temperature, relative humidity, and ultraviolet (UV) index significantly impact crop quality. The absence of adequate ventilation mechanisms in greenhouses presents a challenge for temperature regulation. This study proposes a solution for tropical greenhouses by designing a system that automatically activates fans when temperatures rise above 30 °C. This system regulates temperature and cultivates optimal growth conditions for crops. It is supported by a web page that enables monitoring and adjustment of microclimate data. To accommodate individual crop requirements, the minimum temperature threshold for fan activation can be modified, enhancing the system's adaptability. The impact of the UV index on greenhouse temperature is also considered. The automation system decreases the temperature by around ±3 °C when the UV index hits 10. Nonetheless, its cooling impact wanes beyond the UV index of 10. A greenhouse automation system, equipped with fans and internet access, proves quite useful for agricultural environment management. It tackles the temperature control issue and offers varied solutions.